The English girl : a novel - Silva, Daniel, 1960- (New York : HarperCollins, 2013)
When a young British woman vanishes on the island of Corsica, a prime minister's career is threatened with destruction. Gabriel Allon, master art restorer, spy, and assassin, is thrust into a game of shadows where nothing is what it seems, and the only thing more dangerous than his enemies might be the truth.
Keywords: Allon, Gabriel (Fictitious character) -- Fiction; Intelligence officers -- Fiction; Art restorers -- Fiction; British -- Crimes against -- Fiction; Young women -- Crimes against -- Fiction; Missing persons -- Fiction; Murder -- Investigation -- Fiction; Corsica (France) -- Fiction; Suspense fiction; Spy stories